FOXM1/KIF20A axis promotes clear cell renal cell carcinoma progression via regulating EMT signaling and affects immunotherapy response - Kai Fang; Min Gong; Dong Liu; Shengjie Liang; Yang Li; Weicong Sang; Rujian Zhu (Heliyon, 2023)
Background: The correlation between FOXM1 and KIF20A has not been revealed in clear cell renal cell carcinoma (ccRCC). Methods: Public data was downloaded from The Cancer Genome Atlas (TCGA) database. R software was utilized for the execution of bioinformatic analysis. The expression levels of specific molecules (mRNA and protein) were detected using real-time quantitative PCR (qRT-PCR) and Western blot assays. The capacity of cell growth was assessed by employing CCK8 and colony formation assay. Cell invasion and migration ability were assessed using transwell assay. Results: In our study, we illustrated the association between FOXM1 and KIF20A. Our results indicated that both FOXM1 and KIF20A were associated with poor prognosis and clinical performance. The malignant characteristics of ccRCC cells can be significantly suppressed by inhibiting FOXM1 and KIF20A, as demonstrated by in vitro experiments. Moreover, we found that FOXM1 can upregulate KIF20A. Then, EMT signaling was identified as the underlying pathway FOXM1 and KIF20A are involved. WB results indicated that FOXM1/KIF20A axis can activate EMT signaling. Moreover, we noticed that FOXM1 and KIF20A can affect the immunotherapy response and immune microenvironment of ccRCC patients. Conclusions: Our results identified the role of the FOXM1/KIF20A axis in ccRCC progression and immunotherapy, making it the underlying target for ccRCC.